Symbolism in the Samaria ivories and architecture - D. N. Pienaar (Acta Theologica)
Situated at the crossroads of great nations, the Land of Israel was exposed to numerous external influences. Samaria, the capital city of Northern Israel, was also situated on a major trade route. Various expeditions uncovered approximately 500 pieces of carved ivory in the palace complex at Samaria. According to the motifs carved in them, these pieces can be divided into two main groups. The first group is categorised by the Harpocrates medallion. The Hah and Isis and Nephtys plaques are also relevant in this case. The second group consists mainly of the so-called Woman at the Window, the Winged Sphinx, Winged Figures in Human Form, Horus and Ma’at, the Lion and Bull Plaques, as well as the Tree of Life Motif in ivory. The latter is also represented in the Proto-Ionic capitals uncovered at many different sites, including Samaria. This article discusses the different cultural influences and motifs, and explains their presence.